Maxillofacial Protheses in the Aesthetic-functional Rehabilitation of Cancer Patients : Próteses Bucomaxilofaciais na Reabilitaçâo Estético-Funcional de Pacientes Oncológicos (Naval Dental Jounal, 2022)
Introduction: Maxillofacial prostheses are a therapeutic option for repairing affected structures in the facial and/or intraoral region of cancer patients submitted to surgery. Objective: To report the use of maxillofacial prosthetics in the aesthetic-functional rehabilitation of cancer patients. Case reports: The first two cases show extraoral rehabilitations using adhesive silicone prosthetics in female patients. The first one, an 83-year-old woman, diagnosed with basal cell carcinoma in the right nasal wing, who underwent surgical resection and was rehabilitated with a nasal prosthesis 7 months ago. The second case refers to a 51-year-old female, diagnosed with multiple sclerodermiform basal cell carcinomas, treated with surgery and rehabilitated with a facial prosthesis 8 months ago. The third case addresses the rehabilitation of a 58-year-old female patient, diagnosed with squamous cell carcinoma of the hard palate, treated with surgery and radiotherapy. She was rehabilitated 1 year and 6 months ago with a polymethylmethacrylate obturator prosthesis. Conclusion: The presented cases show that maxillofacial prostheses are essential tools in the reestablishment of esthetics and function of cancer patients, as well as their contribution to psychological issues, in the process of reinsertion in social life and by improving the quality of life of these individuals. Furthermore, they confirm the importance of inserting the dentist in the multidisciplinary oncology team, with an emphasis on postoperative rehabilitation through maxillofacial prostheses.